(untitled) (Terr@ Plural, 2019)
Socio-spatial segregation is a characteristic problem of the Brazilian urbanization process and with the advances of this process, the medium-sized cities have become a space where social exclusion has become a mark of urban reproduction. Public policies have developed and still play an important role in structuring and restructuring the urban space of these cities. This article proposes a brief reflection about the role of public policies of different spheres of power as the facilitator of social and spatial disparities in medium cities from the analysis of Dourados in the Midwest region of the country.